The impact of maternity training on knowledge, confidence, and empowerment: A mixed method pilot evaluation. Issue 1 (5th July 2019) - Jomeen, Julie; Jones, Catriona; Martin, Colin R.; Ledger, Sara; Hindle, Grace; Lambert, Carol
Abstract: Rationale, aims, and objectives: Maternity training is a critical global issue. In the United Kingdom (UK), the need for safer care and patient safety is emphasized through NHS policy. Health Education England (HEE) recommends that training should support a culture of continuous learning and improvement, particularly in the area of reducing the rates of stillbirths, neonatal and maternity deaths, and other adverse outcomes, such as intrapartum brain injuries. Training has been shown to play a crucial role in improving quality of care and reducing maternal and perinatal mortality and morbidity. This evaluation was undertaken to determine both the immediate and sustained impact of multiprofessional training in cardiotocograph (CTG) interpretation and community‐based simulation training in obstetric emergencies: childbirth emergencies in the community (CEC). The impact was measured in terms of practitioner knowledge, confidence, and empowerment immediately pretraining and posttraining and at 12 weeks following training. Methods: A longitudinal mixed methods design was used. Attendees to maternity training sessions on cardiotocograph interpretation and management of childbirth emergencies in the community provided the sample. Quantitative data were collected using questionnaires to assess knowledge, confidence, and empowerment. Qualitative data were collected using open‐ended questions embedded in the questionnaires. Quantitative data were analysed using within‐subject t test to compare differences in the dependent variable measures. Qualitative data analysis was guided by Braun and Clarke (2013) method thematic analysis. Results: The combined qualitative and quantitative results lucidly highlight that training positively impacts upon knowledge, confidence, and empowerment, an impact which is observed across three time points. Conclusions: Training in CTG and CEC is effective in improving knowledge, confidence, and empowerment across all groups. Furthermore, the provision of training packages in these subject areas facilitates improvements in the longer term.